Democracy, Citizenship and Local Press: The Case of the USA “Local Press in Boulder” - Gürses, Fatma (Scientific Research Publishing, Inc., 2015)
Nowadays, democracy discussions including a variety of different approaches are made due to the impact of globalization. In this respect, local press comes to the fore as a significant element in the development of participatory citizenship and democracy values from the periphery to the center in a way to reflect differences. This research aims at examining the relationship amongst democracy, citizenship and local press using the local media Boulder, a city in Colorado state of the USA, as a case study. The study is composed of two parts. In the first part, we are going to discuss theoretical frameworks that will help us to better understand the concept of democracy and citizenship, the impact and importance of participatory citizenship on democracy and democratization. The second part includes the historical development of Boulder city and Colorado state. Their sociological and economic features in order to understand the local background of the geography in which the newspaper we examine in our case study are located. The significance of local media and press in Boulder for the state in general and its historical development are analyzed also including examples including the flow of information rendering the participation of citizens possible. In this respect, the importance of local press for the participation of citizens and its impact on democratization are examined.
Keywords: 11. Sustainability; 16. Peace & justice